TRANSFORMASI MANAJEMEN SUMBER DAYA APARATUR DALAM MENINGKATKAN KINERJA PEMERINTAH DI KABUPATEN BANDUNG BARAT PROVINSI JAWA BARAT - Yunita Nur Fadilla; Muhammad Ilham; Yudi Rusfiana; Ella Wargadinata (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2026)
This research was conducted to examine how the transformation of civil servant human resource management contributes to enhancing the performance of the local government in West Bandung Regency. The study adopted a mixed-methods strategy utilizing an explanatory sequential framework, in which quantitative analysis was first carried out on data obtained from 99 civil servants through the PLS-SEM approach and subsequently reinforced with qualitative interview findings. Within this investigation, the transformation variable was conceptualized through six core dimensions, whereas governmental performance was assessed using indicators encompassing service quality, work quantity, punctuality, cost efficiency, supervisory dependency, and interpersonal influence. The empirical results indicate that the transformation of civil servant resource management exerts a statistically significant and positive impact on regional governmental performance (β = 0.832; p < 0.001). Furthermore, managerial cultural values together with leadership patterns emerged as the most influential determinants in driving organizational performance enhancement. The findings further suggest that improvements in public sector performance are more substantially shaped by shifts in organizational culture and employee conduct rather than relying solely on bureaucratic structural reform. These findings indicate that the success of bureaucratic reform should be directed toward strengthening organizational culture and transformational leadership integrated with merit systems and digital governance.